Study of The Feasibility of Minimarkets in Pontianak Cities Based on the Microbiological Quality of Air In Relation to the Physical Condition of the Room - Siti Almira Rahminda; Jumiati Jumiati; Aini Sulastri (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2023)
Indoor air quality affects human health and productivity. The presence of microorganisms in indoor air is influenced by physical parameters of the space, activities within the space, building factors, ventilation systems, and human maintenance and care. This study aims to assess air quality and analyze the difference in the number of bacteria between minimarkets and the relationship test with their influencing factors. The study used a cross sectional method with 4 minimarket samples, 2 AC and 2 non-AC. Airborne bacterial colony counts were measured using a passive method with blood agar media, a contact time of 15 minutes, and 3 days of repetition. The average value of airborne bacterial colony counts in non-air-conditioned minimarkets (294.3 CFU/) was lower than in air-conditioned minimarkets (531.8 CFU/). The Rank Spearman correlation test results indicated that there was no significant relationship between airborne bacterial colony counts and temperature (p=0.498), humidity (p=0.089), light intensity (p=0.948), and visitor count (p=0.481). All studied minimarkets met the microbiological air quality, population density, and air circulation standards, but not all met the standards for room temperature, humidity, and light intensity based on the quality standards of the Indonesian Ministry of Health Number 1405/MENKES/SK/XI/2002.